DIGITAL TRANSFORMATION IN THE RECAPITULATION OF PUBLIC CONSULTATION FORUMS - Amanda, Medina Nur; Saefulrahman, Iyep; Tiyan Rahmanul Hakim, (Jurnal Governansi, 2025)
Digital transformation is an urgent necessity in public service governance to reduce administrative burdens, improve accuracy, and strengthen accountability. This study examines the recapitalization process of the Public Consultation Forum (Forum Konsultasi Publik/FKP) at the Ministry of Administrative and Bureaucratic Reform, with the unit of analysis focusing on the Deputy Assistant for Community Participation Empowerment (Asdep PPM). The objectives are to analyze the existing recap process, identify the barriers to digitalization, and formulate a strategic model aligned with the principles of the Electronic-Based Government System (SPBE). This research employs a qualitative approach with a case study design, utilizing in-depth interviews, process observation, and document analysis. The findings reveal that digital systems based on online forms, automated spreadsheets, and centralized storage improve efficiency, accuracy, and data traceability while enhancing transparency and accountability. The challenges identified include infrastructure limitations, human resource readiness, regulatory synchronization, organizational resistance, and information security concerns. Applying Kurt Lewin’s change management theory, the study highlights that the success of digital transformation depends on a consistent unfreeze–change–refreeze process within the bureaucracy. The study concludes that digitalization of FKP recap not only accelerates government responses to public input but also strengthens evidence-based policymaking, enhances citizen participation, and fosters an adaptive bureaucratic culture. The proposed strategic model can be replicated in other public service sectors to accelerate the nationwide implementation of SPBE in Indonesia.